Synaptic Vesicle Proteins and Active Zone Plasticity - Kittel, Robert J.; Heckmann, Manfred (Frontiers in Synaptic Neuroscience, 2016)
Neurotransmitter is released from synaptic vesicles at the highly specialized presynaptic active zone. The complex molecular architecture of active zones mediates the speed, precision and plasticity of synaptic transmission. Importantly, structural and functional properties of active zones vary significantly, even for a given connection. Thus, there appear to be distinct active zone states, which fundamentally influence neuronal communication by controlling the positioning and release of synaptic vesicles. Vice versa, recent evidence has revealed that synaptic vesicle components also modulate organizational states of the active zone. The protein-rich cytomatrix at the active zone (CAZ) provides a structural platform for molecular interactions guiding vesicle exocytosis. Studies in Drosophila have now demonstrated that the vesicle proteins Synaptotagmin-1 (Syt1) and Rab3 also regulate glutamate release by shaping differentiation of the CAZ ultrastructure. We review these unexpected findings and discuss mechanistic interpretations of the reciprocal relationship between synaptic vesicles and active zone states, which has heretofore received little attention.